LEGAL POSITION AND PROTECTION OF WHISTLEBLOWERS IN CROATIAN LAW - Špadina, Helga; Kalafatić, Marina (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
SUMMARY   Legal protection of so-called whistleblowers - persons who disclose or expose information on activity deemed illegal, unethical, or not correct within an organization – in the context of labour relation, is enormously delicate topic that does not cease to attract attention of contemporary labour law. When worker is ready to report corruptive offences, it is necessary to activate mechanism of legal protection of whistleblower from unlawful dismissal and in the same time, to active procedure for determination of corruptive offence with clear safeguards to prevent possible abuses by either worker or employer. The paper looks into regulation of protection of rights of whistleblowers in comparative labour law context and case law of European Court for Human Rights. We also analyse the latest efforts by the European Union in the area of legal protection of whistleblowers, as well as the most important European legal instruments. Through provision of protection to whistleblowers, countries  actually contribute to the protection of public interest, advancement of  good governance and strengthening of rule of law, as well as to enactment of fundamental democratic right to freedom of expression.  In Croatia, almost all publicly known whistleblowers got dismissed and up to date, only one of them was returned to work by court decision. Recently adopted law on protection of whistleblowers might contribute to changes and might provide long-sought legal protection to all those who report on corruptive offences on their workplace. Keywords: protection of whistleblowers, labour law, freedom of expression SAŽETAK Pravna zaštita tzv. zviždača – osoba koje otkriju ili podijele informacije o aktivnostima koje su nezakonite, neetične ili nepravilne unutar organizacije – u kontekstu radnih odnosa, iznimno je delikatna tema koja ne prestaje privlačiti pažnju svih koji se bave izučavanjem suvremenog radnog prava. Kada je radnik spreman prijaviti koruptivno djelo, neophodno je aktivirati mehanizam pravne zaštite zviždača od nezakonitog otkaza i istovremeno, aktivirati postupak određivanja koruptivnog djela sa jasnim mehanizmom i mjerama radno pravne zaštite kako bi se izbjegle moguće zloupotrebe bilo od strane radnika, bilo od strane poslodavca. Ovaj rad istražuje pravnu regulativu zaštite prava zviždača  u kontekstu komparativnog radnog prava i u kontekstu presuda Europskog suda za ljudska prava. Također analiziramo i najnovije napore Europske Unije u području pravne zaštite zviždača, kao i najvažnije europske pravne instrumente. Kroz pravnu zaštitu zviždača, države zapravo doprinose zaštiti javnog interesa, napretku dobre uprave i jačanju vladavine prava, kao i provedbi temeljnog demokratskog prava na slobodu izražavanja. U Republici Hrvatskoj skoro svi javno poznati zviždači otpušteni su sa radnog mjesta zbog prijave nepravilnosti i do danas, samo je jedan od njih sudskom odlukom vraćen na posao. Nedavno usvojeni zakon o pravnoj zaštiti zviždača bi mogao doprinijeti promjenama u tom području i mogao bi osigurati dugo iščekivanu pravnu zaštitu svih koji prijave koruptivna kaznena djela na svom radnom mjestu. Ključne riječi: zaštita zviždača, radno pravo, sloboda izražavanja